PENYELIDIKAN KELAYAKAN KIMIA DAN PENYEBARAN CADANGAN PASIR BESI DAERAH TIKU KABUPATEN AGAM UNTUK BAHAN BAKU SEMEN PADA PT. SEMEN PADANG - Heri Prabowo (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
The purpose of this research is to know the mineral content of iron sand and its spreading both vertically and horizontally with the purpose of providing information and data for local government of Agam district for the development and arrangement of environment along the coast. In order to obtain information about the depth of iron sand can be used geoelectric method because one of the physical properties of metal elements including iron is to have low resistivity. In this study used resistivity mapping method that aims to determine the variation of the arrangement of soil layers vertically and horizontally. The configuration used in this method is Schlumberger configuration. To know the chemical content of iron sand is done by taking samples of iron sand systematically and represented at some point. The sample was analyzed chemical composition by XRF method (X-Ray Fluorescence), then correlated with some surface data, so that the depiction of the quality of iron sand of Tiku Regency. From the interpretation of soil resistivity value on 2 paths it can be concluded that iron sand in Tiku Beach area is in depth 0 - 20 m. Chemical content of iron sand from XRF method analysis shows Fe2O3 percentage of 10 - 35%, with TiO2 content of 1 - 3%. The quality of iron sand can be used as raw material for cement maker.